Metagenomic analyses of microbial structure and metabolic pathway in solid-phase denitrification systems for advanced nitrogen removal of wastewater treatment plant effluent: A pilot-scale study - Yang, Zhongchen; Qi Zhou; Sun, Haimeng; Jia, Lixia; Zhao, Liu; Wu, Weizhong (WATER RESEARCH, 2021)
The pilot-scale solid-phase denitrification systems supporting with poly(3-hydroxybutyrateco-3-hydroxyvalerate) (PHBV) and PHBV-sawdust were constructed for advanced nitrogen removal from wastewater treatment plants (WWTPs) effluent, and the impacts of biomass blended carbon source on microbial community structure, functions and metabolic pathways were analyzed by metagenomic sequencing. PHBV-sawdust system achieved the optimal denitrification performance with higher NO3- - N removal efficiency (96.58%), less DOC release (9.00 +/- 4.16 mg L–(1)) and NH4+-N accumulation (0.37 +/- 0.32 mg L (- 1)) than PHBV system. Metagenomic analyses verified the significant differences in the structure of microbial community between systems and the presence of four anaerobic anammox bacteria. Compared with PHBV, the utilization of PHBV-sawdust declined the relative abundance of genes encoding enzymes for NH4+-N generation and increased the relative abundance of genes encoding enzymes involved in anammox, which contributed to the reduction of NH4+-N in effluent. What's more, the encoding gene for electrons generation in glycolysis metabolism obtained higher relative abundance in PHBV-sawdust system. A variety of lignocellulase encoding genes were significantly enriched in PHBV-sawdust system, which guaranteed the stable carbon supply and continuous operation of system. The results of this study are expected to provide theoretical basis and data support for the promotion of solid-phase denitrification. (C) 2021 Elsevier Ltd. All rights reserved.